2017
DOI: 10.1111/beer.12175
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation into the role of trust in collusion

Abstract: Trust has traditionally been regarded as conducive to ethical decision making. However, empirical studies on the relationship between trust and ethical decision making are rare, especially those concerning the negative effects of trust. Therefore, our study aimed to provide empirical evidence in this area. An experiment was designed to investigate whether trusted parties are more likely than non-trusted parties to enter into a collusion that will have unfair consequences for a third party. The results showed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…Only limited attention has been paid to investigating trust decay from a network perspective, as outlined by the low count of occurrence of trust decay studies in Table 1. In the review, only two studies shed light on this topic (Lee & Chuang, 2018;Yenkey, 2018). After the occurrence of a trust violation, Yenkey (2018) found that the relations between the victim (trustor) and violator (trustee) affect the formation and diffusion of distrust.…”
Section: Trust Decaymentioning
confidence: 99%
See 1 more Smart Citation
“…Only limited attention has been paid to investigating trust decay from a network perspective, as outlined by the low count of occurrence of trust decay studies in Table 1. In the review, only two studies shed light on this topic (Lee & Chuang, 2018;Yenkey, 2018). After the occurrence of a trust violation, Yenkey (2018) found that the relations between the victim (trustor) and violator (trustee) affect the formation and diffusion of distrust.…”
Section: Trust Decaymentioning
confidence: 99%
“…The study of Yenkey (2018) suggests that dyadic relational characteristics, such as ties strength and reciprocity, affect trust decay. Apart from dyadic factors, another study by Lee and Chuang (2018) indicates that third parties play a role in trust decay. Lee and Chuang (2018) considered the loss of benefits of a third party when they investigated immoral behaviors between a trustor and a trustee.…”
Section: Trust Decaymentioning
confidence: 99%
“…We tried to exclude other possible explanations. First, gender composition may influence the results, as previous research (Cagle & Baucus, 2006;Lee & Chuang, 2018) has shown that women are less tolerant of unethical behavior than men. However, the chi-square test showed that there was no significant difference in gender composition among the three groups, χ 2 (2, N = 149) = .16, p = .92.…”
Section: Findings Of Studymentioning
confidence: 99%
“…They also point to the fact that little to no attention was devoted to understand how groups make ethical choices and to explore the way in which individual preferences, interpersonal interactions, and social influence shape group decisions. Empirical research on group ethical decisions rather looked at the role of peer influences, significant others, and referent groups on individual choices (Lee & Chuang, 2018; Lehnert et al., 2015; Schminke & Wells, 1999). For example, Mihelič and Cuilberg (2019) answer the call for more research on social factors related to ethical choice, yet, their study focuses on social loafing and its antecedents.…”
Section: Introductionmentioning
confidence: 99%